Nanoengineered biomaterials for repair and regeneration of orthopedic tissue interfaces. (15th September 2016) - Cross, Lauren M.; Thakur, Ashish; Jalili, Nima A.; Detamore, Michael; Gaharwar, Akhilesh K.
Graphical abstract: Abstract: Orthopedic interface tissue engineering aims to mimic the structure and function of soft-to-hard tissue junctions, particularly bone-ligament, bone-tendon, and bone-cartilage interfaces. A range of engineering approaches has been proposed to mimic the gradient architecture, physical properties and chemical characteristics of interface tissues using conventional polymeric biomaterials. Recent developments in nanomaterials and nanofabrication technologies introduce a range of synthesis and fabrication tools to effectively engineer the structure and function of native tissue interfaces. In this review, we will focus on nanoengineered strategies used to replicate the structural and functional aspects of native biological tissues for engineering bone-cartilage, bone-ligament, and bone-tendon interfaces. This review will also highlight some of the emerging applications and future potential of nanomaterials and fabrication technologies in engineering tissue interfaces. Statement of Significance: A major challenge in engineering interfaces is to control the physical and structural characteristics of an artificial environment. The use of nanomaterials and nanoengineered strategies allow for greater control over the changes in structure and function at molecular and nanometer length scale. This review focuses on advanced nanomaterials and nanofabrication approaches developed to emulate bone-cartilage, bone-ligament, and bone-tendon interface regions. Some of the emerging nanoengineered biomaterials proposed to mimic tissue interfaces are also highlighted.